(3GdZQjH GdeUfas - (3GdbGSe Hf SdGe GdgQhj GdCROj GdNRGYj, CHh YHjO, J (B224 (3g` s ((3eSYhO Hf eMeO Hf MGeO s)
(3ChdgG (B:s
(3jHJOF HHGH GdGHf s
(3BNQgG (B:s
(3jfJgi HHGH eKGd eZhdG s
(3MGO HBNQgG Cf fSNI GdCUd JfJgi fMh (B230 (3hQbI GdMb HgG GdfGSN eG hO Yf fSI CNQis
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B101s
Keywords: (3GddZIs